Chelating Agent Functionalized Substrates for the Formation of Thick Films via Electrophoretic Deposition - Mills, Sara C.; Starr, Natalie E.; Bohannon, Nicholas J.; Andrew, Jennifer S. (Frontiers in Chemistry, 2021)
Incorporating nanoparticles into devices for a wide range of applications often requires the formation of thick films, which is particularly necessary for improving magnetic power storage, microwave properties, and sensor performance. One approach to assembling nanoparticles into films is the use of electrophoretic deposition (EPD). This work seeks to develop methods to increase film thickness and stability in EPD by increasing film-substrate interactions via functionalizing conductive substrates with various chelating agents. Here, we deposited iron oxide nanoparticles onto conductive substrates functionalized with three chelating agents with different functional moieties and differing chelating strengths. We show that increasing chelating strength can increase film-substrate interactions, resulting in thicker films when compared to traditional EPD. Results will also be presented on how the chelating strength relates to film formation as a function of deposition conditions. Yield for EPD is influenced by deposition conditions including applied electric field, particle concentration, and deposition time. This work shows that the functionalization of substrates with chelating agents that coordinate strongly with nanoparticles (phosphonic acid and dopamine) overcome parameters that traditionally hinder the deposition of thicker and more stable films, such as applied electric field and high particle concentration. We show that functionalizing substrates with chelating agents is a promising method to fabricate thick, stable films of nanoparticles deposited via EPD over a larger processing space by increasing film-substrate interactions.